Fuzzy logic based intelligent temperature controller for cassava post-harvest storage system - Babawuro, Adamu Y.; Umar, Sambo A.; Sado, Fatai; Salami, Momoh Jimoh Eyiomika; Sidek, Shahrul Na'im (2015)
Significant amount of stored agricultural products are lost as a result of poor and inefficient storage systems in most developing countries, especially in tropical regions of the world. Improvements on the existing storage methods is important to guarantee food security. This study proposes the development of intelligent temperature control technique for fresh cassava roots crop post-harvest storage system using fuzzy logic controller (FLC). The intelligent controller which has two inputs (error in temperature and rate of change in the error) and one output (change in fan speed) was simulated with the developed storage system model for temperature control of fresh cassava roots crop. The results obtained shows that the controller can track appropriately the reference temperature and also gives good stability and robustness towards input disturbances. Faster response to maintain the storage temperature within acceptable limit close to reference point was also achieved successfully.